Pengumpulan Data Penelitian Tindakan Kelas Sebagai Literasi Pendidikan Agama Islam - batubara, Bitcar; Gustafaruddin (Educatia : Jurnal Pendidikan dan Agama Islam, 2024)
Classroom action research (CAR) is a method often used in education to improve the quality of learning through a cycle of planning, action, observation, and reflection. Data collection in PTK is very important to understand learning problems and evaluate the effectiveness of the actions taken. This article discusses in depth the data collection techniques which include observation and interview. The observation technique consists of two types, namely participant and non-participant. Participant observation involves the researcher in the same activities as the participants, so the data obtained is more complete. In contrast, non-participant observation is carried out without the direct involvement of the researcher, only by recording and analyzing the behavior of the subject. In addition, interviews were used to explore in-depth information from subjects related to the learning process and outcomes. By combining these two methods, the data obtained becomes more comprehensive and valid, so that it can support a more objective reflection process and continuous improvement in learning. This article hopes to provide a better understanding of the importance of data collection in PTK and how the implementation of observation and interviews can improve the quality of educational research.